Road warriors to digital nomads: portable computers, habitats, and remote work - Hong, Renyi (Cultural studies (London, England), 2023)
This article focuses on two users of early portable computers - the 'road warrior' and 'digital nomad' of the 1980s and 90s - to illustrate how portability has served an imperialist function in engineering a world fit for buffering privileged subjects against conditions of existential precariousness. The label 'road warriors' emerged in the early history of portable computers as a reaction against the hostile environs of airports and aeroplanes, spaces that were deemed unaccommodating to the use of laptops. These complaints made clear the importance of portable milieus, spaces that had to come into existence to accommodate the transversal of portable computers. The article examines how these emergent portable milieus functioned also as pedagogical habitats, worldly enclosures that guided white, middle/upper-classed, male executives on the means to adapt to a precarious economic existence. Drawing from computer magazines, news articles, and the manifesto Digital Nomad, the article illustrates how these habitats romanticized the value of remote workers, legitimated their transformation of environments, and laid a foundation for the world to be engineered as a buffer for privileged populations. The trend of digital nomadism today which seeks to create opportunities for the austere good life amidst endemic economic problems in the West, speaks to the currency of this imaginary and the longstanding politics of remote work, ushered in by portable computers.